1994
DOI: 10.2105/ajph.84.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Cancer screening among African-American women: their use of tests and social support.

Abstract: This study examined associations between social ties (as measured by the Social Network Index), instrumental and emotional support, and the use of three female cancer screening tests: mammography, cervical smear, and clinical breast examination. Data were taken from a household survey of 670 African-American women living in northern California in 1986. In multiple logistic regression models, Berkman's index was associated with increased use of mammography but not with the use of cervical smear or clinical brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 9 publications
7
45
1
Order By: Relevance
“…For example, several women expressed provider recommendations and motivation from family and friends facilitated their adherence to cancer-related care. These findings corroborate previous studies demonstrating the effectiveness of provider recommendations 18,24,36 and social networks 31,37,38 in catalyzing cancer screening uptake and follow-up. While the impact of social networks on cancer care remains mixed in the literature, Allen et al found perceived approval of family and friends and the perception that screening was normative among one's age group were positively associated with recent mammogram use.…”
Section: Discussionsupporting
confidence: 90%
“…For example, several women expressed provider recommendations and motivation from family and friends facilitated their adherence to cancer-related care. These findings corroborate previous studies demonstrating the effectiveness of provider recommendations 18,24,36 and social networks 31,37,38 in catalyzing cancer screening uptake and follow-up. While the impact of social networks on cancer care remains mixed in the literature, Allen et al found perceived approval of family and friends and the perception that screening was normative among one's age group were positively associated with recent mammogram use.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies examining the effect of social networks on cancer screening behavior in general have generated mixed results, with some studies identifying a positive effect (Kang and Bloom, 1993;Kang et al, 1994;Suarez et al, 1994;Kinney et al, 2005), others and others observing no effect. The current study showed that respondents with a larger social network were more likely to be in the contemplation/action/maintenance, and the :http://dx.doi.org/10.7314/APJCP.2013.14.10.6095 Social Network and Gastric Cancer Screening Behavior in Koreans relapse risk/relapse stages versus the precontemplation stage.…”
Section: Discussionmentioning
confidence: 99%
“…For our purposes, the most pertinent of these potential additional factors is the nature of an individual's social setting or group. Many researchers to date have confirmed that the presence of a social network appears to be a positive indicator of screening (Bloom 1984, Lichtman 1987, Spiegel 1989 Kang et al 1994, and many others). The unifying feature of these studies for our needs is that they look at whether an individual's exposure to a large social network of a given type leads to greater participation.…”
Section: Introductionmentioning
confidence: 89%